2016
DOI: 10.2147/ijn.s101366
|View full text |Cite
|
Sign up to set email alerts
|

Molecular magnetic resonance imaging of activated hepatic stellate cells with ultrasmall superparamagnetic iron oxide targeting integrin αvβ3 for staging liver fibrosis in rat model

Abstract: Purpose To evaluate the expression level of integrin α v β 3 on activated hepatic stellate cells (HSCs) at different stages of liver fibrosis induced by carbon tetrachloride (CCl 4 ) in rat model and the feasibility to stage liver fibrosis by using molecular magnetic resonance imaging (MRI) with arginine-glycine-aspartic acid (RGD) peptide modified ultrasmall superparamagnetic iron oxide nanoparticle (USPIO) specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…In addition, TGF-β1 is considered a key factor in accelerating hepatic fibrosis because it is released from activated HSCs and further stimulates them [ 40 ]. In this study, we found that integrin α v β 3 , α-SMA, and TGF-β1 expression increased with the progression of liver fibrosis, which is similar to previously reported results [ 41 , 42 ]. Moreover, most integrin α v β 3 is expressed in activated HSCs; much less α v β 3 is expressed in qHSCs, hepatocytes, and other non-parenchymal cells [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, TGF-β1 is considered a key factor in accelerating hepatic fibrosis because it is released from activated HSCs and further stimulates them [ 40 ]. In this study, we found that integrin α v β 3 , α-SMA, and TGF-β1 expression increased with the progression of liver fibrosis, which is similar to previously reported results [ 41 , 42 ]. Moreover, most integrin α v β 3 is expressed in activated HSCs; much less α v β 3 is expressed in qHSCs, hepatocytes, and other non-parenchymal cells [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recent achievements in targeted molecular MR imaging offer new strategies to enhance specificity and contrast for detecting such small lesions[7-11]. One of the most commonly studied HCC-targeted MRI systems utilizes antibody (aptamer)-guided iron oxide nanoparticles as probes, which are intended to bind specifically with unique overexpressed HCC-related antigens or genes, such as alpha-fetoprotein (AFP) or glypican-3 (GPC3)[12-15].…”
Section: Introductionmentioning
confidence: 99%
“…And the elevated uptake correlated well with the mRNA and protein levels of integrin α v and β 3 . Ultrasmall superparamagnetic iron oxide nanoparticles (USPIO) modified by RGD (RGD-USPIO) were designed as a molecular MR T2 contrast agent and were used for staging liver fibrosis in rat models induced by CCl 4 [ 69 ]. A significant difference was observed in the T2* relaxation rate change (ΔR2*) among rat treatment cohorts receiving CCl 4 for 0, 3, 6, and 9 weeks.…”
Section: Molecular Probes For Imaging Of Fibrosis and Fibrogenesismentioning
confidence: 99%